THE USE OF INNOVATIVE TECHNOLOGIES BY ENGLISH LANGUAGE TEACHERS IN THE PRACTICAL ORGANIZATION OF ENGLISH LESSONS - Mirzaxalova Sohibaxon Davronbek qizi; Mirzakhalova Sohibakhon (TADQIQOTLAR.UZ, 2024)
Annotation:This article highlights several ways to learn English effectively and some of the modern learning technologies in language learning as well.